(untitled) (Research, Society and Development, 2020)
The objective of this study was to evaluate the effect of different prey concentrations (50; 100; 150 and 200 artemia nauplii post-larvae-1 day-1) and salinized water (0; 1 and 2 g L-1) on larviculture of Pyrrhulina brevis, an Amazonian ornamental fish. The experiment was carried out in a completely randomized design, in a 4x3 factorial design, with three replicates. A total of 360 post-larvae were randomly distributed in 36 aquariums (1L), to 10 post-larvae L-1. At the end of the experimental period (15 days) the post-larvae were measured, weighed and counted. No interaction was identified between the prey concentrations and salinized water for all evaluated parameters. The best growth results, both for length and weight, were observed in the post-larvae that received 150 and 200 artemia nauplii post-larvae-1 day-1, while the lower survival rate was observed in post-larvae fed 50 and 100 artemia nauplii post-larvae-1 day-1. The final length and length gain were higher when the post-larvae were reared in salinized water at 1 and 2 g L-1, while the final weight, weight gain and specific growth rate were higher in post-larvae submitted to 1 g L-1 of salinized water. The uniformity of the batch for weight and length of the fish showed no significant difference, independent of the prey concentrations and salinized water used. Thus, the supply of 150 artemia nauplii post-larvae-1 day-1 in salinized water at 1 g L-1 is recommended during the first fed of Pyrrhulina brevis.